2014
DOI: 10.5424/sjar/2014124-5545
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of udder morphology, alveolar and cisternal milk compartment during lactation and their relationship with milk yield in Najdi sheep

Abstract: A total of 30 multiparous Najdi ewes were used to study the evolution of udder morphology traits and milk fractions in the udder during suckling (3rd, 6th, 9thwk) and milking (10th, 11th, 12thwk) periods. During suckling period, daily milk yield was estimated by using the double oxytocin injections method 4-h after milking. During milking period, ewes were hand-milked once daily. Udder and teat morphology traits for all ewes were measured 4-h after milking. Udder compartments were evaluated 8-h after milking b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
17
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 24 publications
4
17
2
Order By: Relevance
“…The increased milk protein content during lactation was in agreement with the results obtained by Gargouri et al (1993) and Ayadi et al (2014), who found that milk protein content during the suckling period was lower than in the milking period. The average milk fat percentage (4.41%) in this trial was similar to the value reported by Abd Allah et al (2011) in Chios ewes and Ayadi et al (2014) in Najdi ewes, but was lower than the values (6.2-7.4%) reported by Nudda et al (2002) in Awassi ewes and Castillo et al (2009) in Lacaune and Manchega ewes. Breed differences and diet could explain the discrepancies in fat percentages between these results and those of previous studies.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The increased milk protein content during lactation was in agreement with the results obtained by Gargouri et al (1993) and Ayadi et al (2014), who found that milk protein content during the suckling period was lower than in the milking period. The average milk fat percentage (4.41%) in this trial was similar to the value reported by Abd Allah et al (2011) in Chios ewes and Ayadi et al (2014) in Najdi ewes, but was lower than the values (6.2-7.4%) reported by Nudda et al (2002) in Awassi ewes and Castillo et al (2009) in Lacaune and Manchega ewes. Breed differences and diet could explain the discrepancies in fat percentages between these results and those of previous studies.…”
Section: Resultssupporting
confidence: 92%
“…Similar reductions in the daily milk yield, ranging from 30% to 75%, have been reported in several sheep breeds (Gargouri et al, 1993;Ayadi et al, 2011Ayadi et al, , 2014.The drop in daily milk productivity after weaning could be explained by the partial disappearance of the stimulus caused by the transition from suckling to milking. According to Marnet (1997), the decrease in milk yield during weaning might be explained by the reduced emptying frequency and to a lesser degree by dam-lamb separation.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…During milking, the presence of the neuroendocrine milk ejection reflex is crucial for complete emptying of the udder because only 20% of the total milk in cows and above 40% in dairy sheep is located in cisternal compartment after a 12-hour milking interval (Pfeilsticker et al 1996;Marnet and McKusick 2001). The extraction of milk stored in the alveoli is important to obtain maximum milk yield and content of fat also in sheep (Antonic et al 2013;Ayadi et al 2014).…”
mentioning
confidence: 99%